Energy management of commercial buildings – A case study from a POET perspective of energy efficiency - Xia, Xiaohua; Zhang, Jiangfeng; Cass, William (Journal of Energy in Southern Africa, 2017)
This paper aims at analyzing the energy management activities for commercial buildings of a financial service company in South Africa by energy efficiency in terms of performance, operation, equipment and technology (POET). The sustainability of a general energy management program is discussed within this POET framework. As an application of this discussion to the commercial building scenario, the award winning energy management program of this financial service group company is featured from the POET perspective of energy efficiency. The case study shows that the POET based framework can not only cover all major energy management activities, but also identify further energy efficiency improvement opportunities.